The Strategy of Tanah Pusaka Care Forum Movement in Creating Adat Village in Grajakan Village Banyuwangi Regency - Irawan, Deky Yoga; Ganefo, Akhmad (Laboratorium Sosiologi FISIP Universitas Jember, 2018)
The phenomenon of social movement in Tanah Pusaka region locates in Grajagan village of Banyuwangi regency. The campaign appeared due to Tanah Pusaka community sense of injustice in Grajagan village regarding the land status that they used. This research aims to know and to describe what form of movement strategy and what obstacles in implementing the strategy for struggling. This study used the theory of resource mobilization as well as the method used was descriptive qualitative located in Tanah Pusaka Grajagan village Purwoharjo district of Banyuwangi regency. The research results obtained that the group of Tanah Pusaka Care Forum was formed due to injustice felt by the community of Tanah Pusaka regarding the right status of land ownership. Thus, Tanah Pusaka Care Forum became a social group striving for community goals of Tanah Pusaka community, namely, establishing the indigenous villages in the region of Tanah Pusaka, and creating the prosperous citizens of Tanah Pusaka. Tanah Pusaka Care Forum, organized, attached ideology, gave identity and mobilized the resources. Several strategies that used in maintaining their awareness and developing their networks are field action, lobbying, members’ consolidation, istighosah, mapping the area, and regeneration. The obstacles experienced by Tanah Pusaka Care Forum in the form of the weakening from the external and appearing the restlessness from internal in Tanah Pusaka Care Forum. Keywords: indigenous villager, social movement strategy, and Tanah Pusaka Care Forum. Referensi: Budihardja, Miriam. 2010. Dasar-Dasar Ilmu Politik. Jakarta: PT Gramedia Pustaka Utama. Gardono, Sujatmiko. 2006. Gerakan Sosial, Wahana Civil Society Bagi Demokrasi. Jakarta: LP3ES. Harahap, A. 2004. Hukum Acara Perdata. Jakarta: PT Sinar Grafika. Horton, Paul B. dan Hunt, Chester L.,. 1993. Sosiologi, Terjemahan Aminuddin Ram dan Tita Sobari. Jakarta: Erlangga. Kartasapoetra, G dan Kreimers, LJ. B. 1987. Sosiologi Umum. Jakarta: Bina Aksara. Maarif, Syamsul. 2010. Perilaku Kolektif dan Gerakan Sosial. Yogyakarta: Gress Publishing. Suharko. 2006. Gerakan Sosial Konsep, Strategi, Aktor, Hambatan dan Tantangan Gerakan Sosial di Indonesia. Malang: Averroes Press. Skripsi: Aini, Fadlilathul. 2008. Stretegi dan Platform Gerakan Masyarakat Sipil dalam Situasi Politik Lokal dan Nasional di Yogyakarta. Bogor: Institut Pertanian Bogor.